Jurnal Kata: A deconstructive reading of yasmina reza's art - Behnaz amani (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
this article investigation of derrida's deconstructive strategies on Yazmina's reza's art in which concepts such as difference floating signifiers paradoxes